Community Essay: Sustainable development of the Amazon forest: a fine line between conservation and exploitation? - Christopher Reyer (Sustainability: Science, Practice, & Policy, 2009)
This essay constitutes a piece of boundary work between science and policy. It illustrates the conflicts, but also the opportunities, that natural resource management encounters in the twenty-first century. I have tried to provide a widely accessible document that argues why a more holistic approach to conservation and natural resource management is imperative. Inspired by the concept of “Integrated Forest Management,” I conceived the basics for an “Integrated Sustainable Development” strategy. I have approached the vast topic of “sustainable development in the Amazon” without complicated methodology because I want to present the problem in its inherent complexity and any other manner would largely exceed the length of an essay. A future scientific challenge is to deepen the analysis of why an integrated approach to conservation and ecosystem management is more likely to succeed than a segregative approach. Ultimately, the more political task, however, is to promote dialogue between the manifold and important stakeholder groups in the Amazon to a point where social, ecological, and economic realities are combined and provide a portfolio of sustainable development options.